A validated LC–MS/MS method for the quantification of piperacillin/tazobactam on dried blood spot. (November 2014) - Barco, Sebastiano; Risso, Francesco Maria; Bruschettini, Matteo; Bandettini, Roberto; Ramenghi, Luca A; Tripodi, Gino; Castagnola, Elio; Cangemi, Giuliana
Background Therapeutic drug monitoring (TDM) of antibiotics in children is of fundamental importance for effective patient management. The use of dried blood spot (DBS) offers a number of advantages over conventional blood collection. The aim of this study is to develop and validate a method to measure piperacillin/tazobactam in DBS.Results The analysis was performed by using LC–MS/MS operating in multiple reaction monitoring mode. The method has been validated by applying EMA guidelines and its suitability for TDM was evaluated by using samples from low birth weight neonates.Conclusion This paper describes a fast and cost-effective micromethod for the simultaneous determination of piperacillin/tazobactam levels on dried blood spot that is suitable for TDM in children.